2021
DOI: 10.1101/2021.02.27.21252559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in Thoracic Impedance and Arrhythmia Burden Among Patients with Implanted Cardiac Defibrillators During the COVID-19 Pandemic

Abstract: Hospitalizations for acute cardiac conditions have markedly declined during the coronavirus disease 2019 (COVID-19) pandemic, yet the cause of this decline is not clear. Using remote monitoring data of 4,029 patients with implantable cardiac defibrillators (ICDs) living in New York City and Minneapolis/Saint Paul, we assessed changes in markers of cardiac status among these patients and compared thoracic impedance and arrhythmia burden in 2019 and 2020 from January through August. We found no change in several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…We present evidence that the observed sensor changes are in some way associated with COVID-19 infection because the magnitude of change was significantly different for COVID-positive versus negative and control patients. For instance, although activity significantly decreased among all patient cohorts, likely due to stay-at-home orders limiting activity for all New York City residents as observed in prior studies, 14 we observed a significantly greater decrease in activity for COVID-positive patients. Similarly, we observed distinctly different sensor changes between COVID-positive and COVID-negative patients.…”
Section: Discussionsupporting
confidence: 65%
“…We present evidence that the observed sensor changes are in some way associated with COVID-19 infection because the magnitude of change was significantly different for COVID-positive versus negative and control patients. For instance, although activity significantly decreased among all patient cohorts, likely due to stay-at-home orders limiting activity for all New York City residents as observed in prior studies, 14 we observed a significantly greater decrease in activity for COVID-positive patients. Similarly, we observed distinctly different sensor changes between COVID-positive and COVID-negative patients.…”
Section: Discussionsupporting
confidence: 65%
“…stitial fluid status in pulmonary oedema [224,225] and have been suggested to be a possible marker of disease severity in a very small sample of COVID-19 patients [223]. These preliminary findings deserve larger scale validation.…”
Section: Fig 4 Summary Of Documented Abnormalities On Electrocardiogr...mentioning
confidence: 83%
“…Implantable cardiac defibrillators can assess thoracic impedance by measuring the resistance between the right ventricular lead and the device, traversing significant volumes of lung tissue [223]. Changes in thoracic impedance reflect the interstitial fluid status in pulmonary oedema [224, 225] and have been suggested to be a possible marker of disease severity in a very small sample of COVID‐19 patients [223]. These preliminary findings deserve larger scale validation.…”
Section: Markers Of Pulmonary Dysfunctionmentioning
confidence: 99%